A Stimuli‐Responsive Smart Lanthanide Nanocomposite for Multidimensional Optical Recording and Encryption - Li, Xiang; Xie, Yujie; Song, Bo; Zhang, Hao‐Li; Chen, Hao; Cai, Huijuan; Liu, Weisheng; Tang, Yu (Angewandte Chemie International Edition, 2017)
A stimuli‐responsive lanthanide‐based smart nanocomposite has been fabricated by supramolecular assembly and applied as an active material in multidimensional memory materials. Conjugation of the lanthanide complexes with carbon dots provides a stimuli response that is based on the modulation of the energy level of the ligand and affords microsecond‐to‐nanosecond fluorescence lifetimes, giving rise to intriguing memory performance in the spatial and temporal dimension. The present study points to a new direction for the future development of multidimensional memory materials based on inorganic–organic hybrid nanosystems. Hidden talents: A stimuli‐responsive lanthanide nanocomposite was fabricated by functionalization of carbon dots with lanthanide complexes and applied in a multidimensional memory device. The fluorescence lifetime and color can be changed by modulating the energy levels of the lanthanide ligand.